HUBUNGAN KARAKTERISTIK PETANI DAN TINGKAT ADOPSI TEKNOLOGI PADA USAHATANI BAWANG MERAH DI DESA TONSEWER, KECAMATAN TOMPASO - Alfons ., Manongko; Lyndon ., Pangemanan (AGRI-SOSIOEKONOMI, 2017)
This study aims to analyze the relationship between the characteristics of farmers with the level of adoption and application of technological innovation in onion farming in Tonsewer Village, Tompaso Subdistrict, Minahasa Regency, North Sulawesi Province. This research was conducted from February to March 2017. This research used primary and secondary data. Primary data were collected by interviewing onion farmers using questionnaires. Sampling of 48 people. Analysis method using Descriptive Analysis. The study found that the technological adoption rate in Tonsewer village is very high and has adopted the technology. Factors influencing the adoption rate are land area, farming, income, formal education, non-formal education, age, and cosmopolitan level. Spearman's correlation value of land area, income, formal education, non-formal education and cosmopolitan level shows the direction of positive correlation, while age shows the direction of negative correlation to the adoption rate of onion technology.